A cohort study to identify simple clinical tests for chronic respiratory failure in obese patients with sleep-disordered breathing. Issue 1 (11th April 2014) - Mandal, S; Suh, E S; Boleat, E; Asher, W; Kamalanathan, M; Lee, K; Douiri, A; Murphy, P B; Steier, J; Hart, N
Abstract : Background: Chronic respiratory failure complicating sleep-disordered breathing in obese patients has important adverse clinical implications in terms of morbidity, mortality and healthcare utilisation. Screening strategies are essential to identify obese patients with chronic respiratory failure. Method: Prospective data were collected from patients with obesity-related sleep-disordered breathing admitted for respiratory assessment at a UK national sleep and ventilation centre. Hypercapnia was defined as an arterial partial pressure of carbon dioxide of >6kPa. Results: 245 obese patients (56±13 years) with a body mass index of 48±12 kg/m 2, forced vital capacity (FVC) of 2.1±1.1 L, daytime oximetry (SpO2 ) of 91±6% and abnormal overnight oximetry were included in the analysis. Receiver operator curve analysis for the whole group showed that an FVC ≤3 L had a sensitivity of 90% and a specificity of 41% in predicting hypercapnia, and an SpO2 ≤95% had a sensitivity of 83% and a specificity of 63% in predicting hypercapnia. Gender differences were observed and receiver operator curve analysis demonstrated 'cut-offs' for (1) SpO2 of ≤95% for men and ≤93% for women and (2) FVC of ≤3.5 L for men and ≤2.3 L for women, in predicting hypercapnia. Conclusions: The measurement of FVC and clinic SpO2 in obese patients with abnormal overnight limited respiratory studies predicted hypercapnia. This may have clinical utility in stratifying patients attending sleep clinics.